Revisiting the Vocal Repertoire of Thoropa miliaris and T. taophora (Anura: Cycloramphidae): Insights into the Acoustic Divergence among Lineages - Sabbag, Ariadne Fares [UNESP]; Carvalho, Thiago Ribeiro; Brasileiro, Cinthia Aguirre; Consolmagno, Rafael Camargo [UNESP]; Baptista Haddad, Célio Fernando [UNESP] (Herpetologists League, 2024)
Calls are the most conspicuous form of communication in anurans. They are generally species specific, mediate mating behavior and, as such, are often emitted during the breeding season. The calls of Thoropa, an endemic genus to the Brazilian Atlantic Forest and Campo Rupestre, are known from the type localities of six valid species. However, recent molecular analyses revealed a greater number of molecular lineages within the T. miliaris species group than previously recognized. Here we aimed to investigate the advertisement calls of 12 individuals of T. miliaris and 5 individuals of T. taophora. Whenever possible, these were assigned to the recognized molecular lineages through Sanger sequences of the final portion of the 16S ribosomal mitochondrial gene. The sampled individuals are from different localities and associated with different lineages. We conducted the acoustic characterization based on 15 (T. miliaris) and 11 (T. taophora) recordings. We identified three types of calls: Type 1 and Type 2 calls of T. miliaris, and a third call type, exclusive to T. taophora. Type 1 of T. miliaris is usually formed by an introductory and a long note, followed by a more frequently emitted (i.e., common) note. Type 2 of T. miliaris is composed of an introductory note, followed by a long note, and followed by relatively high and low amplitude alternated notes. The call of T. taophora is formed by a peculiar note, with low and high relative amplitude portions on the same note. It is worth noting that syntopic lineages exhibit similar calls. Also, recorded calls from far localities of the same lineages are similar. This study is the first to analyze calls of different lineages and populations T. miliaris and T. taophora.
Keywords: Advertisement call; Atlantic Forest; Bioacoustics; Brazil; Rock Frogs